1978
DOI: 10.1002/art.1780210302
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia In Systemic Lupus Erythematosus

Abstract: One hundred fifty-eight patients with active, untreated systemic lupus erythematosus (SLE) were studied from the time of diagnosis. Lymphopenia was present in 75%, and another 18% of these patients developed lymphopenia subsequent to disease reactivation. Lymphopenia of less than 1500 cells/pl occurred more frequently than any of the preliminary criteria for the classification of SLE, and it was the most prevalent initial laboratory abnormality. Lymphocyte counts were significantly lower in lupus than in the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
2
2

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(32 citation statements)
references
References 14 publications
(3 reference statements)
4
23
2
2
Order By: Relevance
“…This granulocyte signature was present in about 50% of the SLE patients profiled and included but was not limited to the following genes: AZU, DEFA1, DEFA4, ELA2, MMP8, MMP9, RNAS2, MPO, CAMP, FCAR, and CYBB (Figure 1). The downregulation of T and B cell gene signatures was also observed in WB of SLE patients (Figure 1), and is consistent with the observation of lymphopenia in the peripheral blood of SLE patients that has been previously reported in the literature [13, 20]. Table 3 lists the 50 most downregulated transcripts observed in WB of SLE patients.…”
Section: Resultssupporting
confidence: 89%
“…This granulocyte signature was present in about 50% of the SLE patients profiled and included but was not limited to the following genes: AZU, DEFA1, DEFA4, ELA2, MMP8, MMP9, RNAS2, MPO, CAMP, FCAR, and CYBB (Figure 1). The downregulation of T and B cell gene signatures was also observed in WB of SLE patients (Figure 1), and is consistent with the observation of lymphopenia in the peripheral blood of SLE patients that has been previously reported in the literature [13, 20]. Table 3 lists the 50 most downregulated transcripts observed in WB of SLE patients.…”
Section: Resultssupporting
confidence: 89%
“…Finally, patients with inactive disease had a significantly lower percentage of CD4 + T cells than in HCs (11.79 ± 0.80%, N = 52 vs. 17.12 ± 0.71%, N = 83, respectively, P < 0.0001). These results confirm earlier reports [3-5] that SLE patients present with CD4 + T cell leucopenia correlated with disease activity and showed that it is accentuated by steroid and immunosuppressive treatment, which is by itself associated with disease activity.…”
Section: Resultssupporting
confidence: 92%
“…Multiple studies have shown that these autoantibodies are T cell-dependent with autoreactive CD4 + T cells providing co-stimulatory signals and cytokines such as IL-4 and IL-21 to the autoreactive B cells [1,2]. The CD4 + T cells of SLE patients present many functional defects, which include a reduced number of circulating cells that is associated with disease activity [3-5], impaired signaling [6] and increased spontaneous activation coupled with a hypo-responsiveness upon reactivation [7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…The increased frequency of CD8 + T cells specific for lytic EBV antigens is most likely due to recurrent EBV replication. However, the elevated frequency is counterbalanced by a global T cell lymphopenia, which is a common clinical feature of SLE [25]. Furthermore, functional impairment at the single-cell level coincides with a diminished absolute number of functional EBV-specific CD8 + T cells in SLE patients.…”
Section: Discussionmentioning
confidence: 99%